Competition effect of solid-state stretching induced orientation and phase separation on stereocomplex crystallization of PLLA/PDLA during annealing. (13th March 2023) - Liu, Xiang; Wang, Shitong; Huang, Kai; Liu, Hongmin; Zhang, Xiaozhen; Zou, Lin; Shi, Honghui; Chang, Baobao; Liu, Chuntai
Abstract: Benefiting from its superior thermal and mechanical properties, the stereocomplex crystal (SC) of PLLA/PDLA is catching increasing interest. In this work, a systematic investigation was performed to reveal the effect of solid-state stretching on the formation of SC during annealing. Results show that as the stretching temperature was close to the glass transition temperature ( T s = 60 °C), the polymer chains orientation was increased gradually with draw ratio ( λ ). As a result, the crystallization induction time ( t 0 ) was shortened, the growth rate ( G r ) of SC was enlarged, and the crystallinity of SC ( X SC ) was elevated as a result of orientation-induced crystallization. Whereas, the saturation of t 0, G r, and X SC appeared quickly when λ reached 2.7, although the orientation of polymer chains continued to increase. The reason is that in addition to orientation, strong phase separation between PLLA and PDLA was also triggered therein. The phase separation prohibited greatly the crystallization of SC due to a long time would be needed for PLLA or PDLA chains to diffuse to a distance close enough to activate the hydrogen-bonding interaction, which is the prerequisite of SC crystallization. When the stretching temperature was elevated to 75 °C, the phase separation became much weaker. So X SC was higher compared to that of the blend stretched at 60 °C to the same λ . Moreover, in the annealing temperature from 180 °C–190 °C, t 0 was much smaller for the blend stretched at 75 °C since the crystallization of SC in this temperature range is a diffusion-controlled process. Graphical abstract: Image 1 Highlights: Strong orientation of polymer chains and phase separation are induced by solid-state stretching. Orientation of polymer chains and phase separation exhibit a competition effect on the crystallization of SC. The more intense phase separation at lower stretching temperature gives rise to a longer crystallization. induction time